Living whole-cell catalysis in compartmentalized emulsion. (January 2020) - Zhao, Qingcai; Ansorge-Schumacher, Marion B.; Haag, Rainer; Wu, Changzhu
Graphical abstract: Highlights: A multi-compartmentalized emulsion system was established. The emulsion can be easily prepared by hand shaking, and has good stability. Successful encapsulation of living whole-cells was achieved. Extraordinary large interfacial area of the system allowed efficient biocatalysis. Various reactions were carried out by loading cells expressing different enzymes. Abstract: Whole-cell biocatalysis plays an important role in biotransformation with unique features such as good tolerance of solvents and easy recycling. However, the relatively low catalytic efficiency limits their use in real production. In this study, a multi-compartmentalized emulsion in organic solvent was constructed to encapsulate living cells for enhanced catalytic performance. Extraordinary large interfacial area of the emulsion improved the bioactivity of Escherichia coli (E. Coli) cells up to 137 times compared to a standard biphasic system. The emulsion was stabilized by a biocompatible polymer and prepared by gentle shaking by hand, which resulted in good cell viability. Moreover, the encapsulated cells could be easily recycled, and the activity remained more than 70% after five cycles. This work provides a promising approach for utilizing whole-cell catalysts for efficient organic catalysis.